Progesterona injetável de longa ação associada ao GNRH em protocolo de inseminação artificial em tempo fixo em bovinos - Menezes Bisneto, Bento Martins de (2022)
Intense food production has been required to supply the growing consumption all over the world. Therefore, high technology is required for this production, demanding new agricultural management systems and biotechnological alternatives. The objective of this work was to develop a FTAI protocol with long-acting injectable progesterone and control of follicular development and ovulation with eCG and GnRH. The goal was to obtain, at the end of the experiments, a simple, effective procedure for FTAI, with pregnancy rates among those obtained with traditional methods with an intravaginal progesterone device. In experiment 1, twenty multiparous suckling Brangus cows,70 days postpartum, were allocated in two groups. One group received an intravaginal progesterone device (Group P4IVD; n=10; SINCROGEST®; 1g) and the other group received long-acting progesterone injection (GrupoP4i; n=10; SINCROGEST®; 300mg/SC). The ultrasound evaluation for follicular dynamics was performed daily. Blood was obtained on Day 10, 11 and 15 for P4 evaluation. In experiment 2, seventy multiparous suckling Brangus cows, 70 days postpartum, kept in native field, with a body condition score between 2.5 and 3.5 were allocated in two groups: in one group the cows received an intravaginal progesterone device (Group P4IVD; n=35; SINCROGEST®; 1g) and in the other group the animals were injected a long-acting progesterone (Group P4i; n= 35; SINCROGEST®; 300mg/SC) on day 0. Animals from both groups were inseminated at a fixed time. All statistical analyzes were performed using the JMP statistical package (SAS Institute Inc., Cary, NC), considering a significant level P≤0.05. Follicular growth rates from D6 to D9 did not differ between the vaginal device (1.36 ± 0.17 mm/day) and injectable P4 (1.47 ± 0.17 mm/day; P>0.05) groups. Similarly, ovulation rates did not differ between these two groups (P4IVD 4/10 cows; P4i 5/10 cows; P>0.05). On days 10 and 11, serum progesterone concentrations were higher in animals that received injectable progesterone (D10: 0.36 ± 0.15 and 1.89 ± 0.15 ng/mL, for P4IVD and P4i, respectively; P <0.0001; D11: 0.41 ± 0.11 and 1.59 ± 0.11 ng/mL, for P4IVD and P4i, respectively; P<0.0001). On D15, this difference between the P4IVD (2.63 ± 0.49 ng/mL) and P4i (2.52 ± 0.49 ng/mL) groups in serum progesterone concentration was no longer observed (P>0, 05). However, pregnancy rates at 30 days after FTAI were higher in cows in the P4IVD group (48%) than in those in the P4i group (2%; P<0.05). We conclude that injectable progesterone concentrations remain high in the periovulatory period, which may have caused the low pregnancy rate; however, further experiments should be performed to confirm and adjust the injectable progesterone dose.